2020
DOI: 10.5114/ceji.2020.94712
|View full text |Cite
|
Sign up to set email alerts
|

Infection-induced innate antimicrobial response disorders: from signaling pathways and their modulation to selected biomarkers

Abstract: Severe infections are a major public health problem responsible for about 40-65% of hospitalizations in intensive care units (ICU). The high mortality (30-50%) of persons diagnosed with severe infection is caused by largely unknown mechanisms of sepsis-induced immune system response. Severe infections with dynamic progress are accompanied with SIRS (systemic inflammatory reaction syndrome) and CARS (compensatory anti-inflammatory response syndrome), and require a biological treatment appropriate to the phase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…10 The possible mechanisms of SIRS include: a pro-inflammatory response of inflammatory cytokines; an increased release of toxic substances such as excitatory amino acids, nitric oxide and free radicals; and an increased production of thrombin, which induces glial in neuronal apoptosis of cells. 11,29,30 Previous studies focused on the association between SIRS and the outcomes after ICH. Boehme et al 12 found that patients with SIRS were at an increased risk of poor prognosis, but SIRS was not an independent predictor of poor functional outcomes after ICH.…”
Section: The Logistic Regression Analysis Was Performed To Analyzementioning
confidence: 99%
“…10 The possible mechanisms of SIRS include: a pro-inflammatory response of inflammatory cytokines; an increased release of toxic substances such as excitatory amino acids, nitric oxide and free radicals; and an increased production of thrombin, which induces glial in neuronal apoptosis of cells. 11,29,30 Previous studies focused on the association between SIRS and the outcomes after ICH. Boehme et al 12 found that patients with SIRS were at an increased risk of poor prognosis, but SIRS was not an independent predictor of poor functional outcomes after ICH.…”
Section: The Logistic Regression Analysis Was Performed To Analyzementioning
confidence: 99%
“…Based on the bench-experiments of multiplex immunoassay and flow cytometry analysis in deficient mice, the cytokine production, neutrophil migration, and phagocytic function have been suggested to play critical roles in the pathogenesis of sepsis ( 21 23 ). Cytokines and chemokines including IL-6 ( 24 ), IL-10 ( 7 , 24 ), CD14 ( 17 ), to name a few, were suggested as potential biomarkers for early diagnosis (before organ dysfunction occurs) of sepsis ( 25 ). But due to evolutionary discordance between human and mouse innate immune signaling ( 26 ), these may not necessarily be true biomarkers ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), a type of ncRNAs, are short, single-stranded RNA fragments of 21-23 bases that contribute to the maintenance of homeostasis, regulation of cellular physiological functions, the cell cycle, differentiation, and apoptosis. miRNAs have been implicated to affect in ammatory and antiin ammatory immune responses, such as sepsis, diabetes, tumors, chronic obstructive pulmonary disease, asthma, in ammatory bowel disease, and schizophrenia [12].…”
Section: Introductionmentioning
confidence: 99%